Feminizing chicks: a model for avian sex determination based on titration of Hint enzyme activity and the predicted structure of an Asw-Hint heterodimer - Pace, Helen C (BioMed Central, 2003)
BACKGROUND: In birds and some lizards, females are heterogametic with a ZW karyotype, while males are ZZ homogametes. The molecular basis for sexual differentiation in birds is unknown: arguments exist for doses of Z masculinizing chicks and for W information feminizing. ASW was identified as a tandemly repeated gene conserved on avian W chromosomes that is expressed in early female development and appears to be an inactive form of avian Z-encoded HINT. Hint is a dimeric enzyme that hydrolyzes AMP linked to lysine, whose enzyme activity is required for regulation of the Cdk7 homologous Kin28 kinase in yeast. Of 16 residues most conserved across all life forms for AMP interactions, 15 are sexually dimorphic in birds, that is, altered in the female-specific Asw protein. Genomic and expression data suggest that Asw may feminize chicks, dominantly interfering with Hint function by heterodimerization. RESULTS: We consider whether positive cooperativity could explain how Hint heterodimerization with an inert enzyme might reduce specific activity by more than 50% and provide data sufficient to reject this model. Instead, we hypothesize that Asw carries a signal for mislocalization and/or proteolysis, and/or dominantly suppresses the remaining Hint active site to function as a dominant negative. CONCLUSIONS: Molecular modeling suggests that Asw and Hint can heterodimerize and that Gln 127, an Asw-specific alteration for Trp123, dominantly interferes with the Hint active site. An extra dose of HINT in ZZW chicks, and thus more Hint homodimer, may partially overcome the feminizing influence of ASW and lead to the observed intersexual characteristics of ZZW triploids.